A comprehensive framework and key performance indicators for maintenance performance measurement - Raza, T. (Asian Research Publishing Network, 2016)
Effective maintenance prolongs machine lifetime, enhances equipment availability and retains the equipment in functional condition. Whereas, unreliable maintenance may result in more equipment replacement because of a shorter life. It is important to realize that maintenance function adds value, although not as obvious as other departments and that it is an equally important link as other departments. With those consequences, a good strategy of maintenance is very much needed, which helps to improve and maintain the productivity, quality and most importantly the operational cost. But unfortunately, management faces the challenges of higher maintenance cost, reworks, and unplanned shutdowns due to ineffective performance measurement and owing to the inappropriate decision of management. To make sure the plant attains the targeted performance, maintenance manager requires a better way of maintaining the performance of maintenance functions. This could only be possible through the development and implementation of a well-defined maintenance performance measurement framework and indicators that are capable of measuring the significant elements like maintenance cost, product quality, manufacturing performance, etc. The aim of this paper is to develop a maintenance performance measurement framework which is based on reliability, availability, maintainability and safety (RAMS) parameters and to show that how to calculate the KPIs related to RAMS an excel based template which comes together with list of formulas for every KPI to measure the maintenance performance. This framework will assist managers to measure the maintenance performance measurement which helps them to improve the performance of different maintenance activities and in different areas. Â©2006-2016 Asian Research Publishing Network (ARPN).